2018
DOI: 10.3389/fonc.2018.00587
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Acquired Aplastic Anemia and the Role of the Bone Marrow Microenvironment

Abstract: Aplastic anemia (AA) is characterized by bone marrow (BM) hypocellularity, resulting in peripheral cytopenias. An antigen-driven and likely auto-immune dysregulated T-cell homeostasis results in hematopoietic stem cell injury, which ultimately leads to the pathogenesis of the acquired form of this disease. Auto-immune and inflammatory processes further influence the disease course as well as response rate to therapy, mainly consisting of intensive immunosuppressive therapy and allogeneic hematopoietic cell tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 86 publications
1
47
1
3
Order By: Relevance
“…This study suggested that the destruction of the functionally active HSC, upon exposure to IFNγ, is immune mediated through activated cytotoxic T cells (14). Additionally, it has been suggested that immune-mediated destruction of HSC leads to BMF in aplastic anemia (9). However, in the current study in the context of immune-deficient NSG mice, the lack of functional T, B and NK cells did not attenuate TIRAP-mediated BMF.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…This study suggested that the destruction of the functionally active HSC, upon exposure to IFNγ, is immune mediated through activated cytotoxic T cells (14). Additionally, it has been suggested that immune-mediated destruction of HSC leads to BMF in aplastic anemia (9). However, in the current study in the context of immune-deficient NSG mice, the lack of functional T, B and NK cells did not attenuate TIRAP-mediated BMF.…”
Section: Discussioncontrasting
confidence: 65%
“…Dysregulation of immune responses has been implicated in MDS and other BMF disorders (5,(7)(8)(9)(10). A pro-inflammatory milieu and sensitivity of hematopoietic stem/progenitor cells (HSPC) to inflammatory cytokines such as TNF-α, IL-6 and IFNγ have been shown to suppress normal hematopoiesis (5,11).…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem/stromal cells (MSCs) are heterogeneous populations capable of multipotential differentiation together with hematopoietic supporting and immunosuppressive properties [9][10][11]. MSCs have been wildly used in preclinical and clinical studies for disease remodeling including acute-on-chronic liver failure, diabetes, Crohn's disease, and acquired AA [9,[12][13][14][15][16]. Generally, as the key component in the microenvironment, MSCs serve as a potential supplementary alternative for refractory AA treatment and have exhibited unexceptionably therapeutic effect mainly through transdifferentiation, immunomodulatory activity, autocrine, and paracrine together with providing an ideal niche [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, as the key component in the microenvironment, MSCs serve as a potential supplementary alternative for refractory AA treatment and have exhibited unexceptionably therapeutic effect mainly through transdifferentiation, immunomodulatory activity, autocrine, and paracrine together with providing an ideal niche [17,18]. However, the dysfunction and pathophysiology of MSCs during acquired AA is still obscure [1,14]. As mentioned above, our team and Hamzic et al have identified the MSC's involvement in the dysfunction of HSCs and immunological reconstitution in patients with AA [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Aplastic anemia (AA) is a rare disease, caused by bone marrow (BM) aggression resulting in hypo or aplastic BM with precocious fat replacement and consequently to peripheral blood pancytopenia [1,2]. The autoimmunity process in AA occurs due to the activation of the oligoclonal cytotoxic T cells that will lead the hematopoietic cells to apoptosis.…”
Section: Introductionmentioning
confidence: 99%